2014
DOI: 10.1016/j.jpainsymman.2013.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Reasons for Referral and Activities of Hospital Palliative Care Teams Using a Standard Format: A Multicenter 1000 Case Description

Abstract: The components of hospital PCT activities were successfully measured using the Standard Format for Reporting Hospital PCT Activity. The results of this study and the format for reporting hospital PCT activity could be effective in improving hospital PCT practice and for the education of new hospital PCT members.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 22 publications
(13 reference statements)
4
25
1
1
Order By: Relevance
“…Survival times among the patients who received care between 2007 and 2014 were significantly longer than among the patients who received care between 2000 and 2006, reflecting improvements of care. Specifically, the median survival time of patients receiving care between 2007 and 2014 was 6 months, which was compatible with survival times in previous studies (6,9,12,13). The present team approach, which includes palliative care, was initiated in 2003, and the number of patients receiving this care has gradually increased.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Survival times among the patients who received care between 2007 and 2014 were significantly longer than among the patients who received care between 2000 and 2006, reflecting improvements of care. Specifically, the median survival time of patients receiving care between 2007 and 2014 was 6 months, which was compatible with survival times in previous studies (6,9,12,13). The present team approach, which includes palliative care, was initiated in 2003, and the number of patients receiving this care has gradually increased.…”
Section: Discussionsupporting
confidence: 84%
“…The present median survival time after radiotherapy was 4 months, and was shorter than that reported in previous studies (6,9,12,13). This may reflect the preponderance of advanced metastatic bone tumors and poor general conditions at the start of radiotherapy.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…The circumstances of intervention included its setting (short term or long term inpatient care, outpatient clinics or outpatient services), the reasons for referral and the service requesting consultation. Reasons for referral and problems identified by the team were collected using a common standard format, inspired from Sasahara et al [19] and composed with: physical symptoms (pain, dyspnea, …), psychological symptoms, adaptation of symptomatic treatment, social issues, ethical questions, problems related to information of the patient or his/her family, decision for place of care, early encounter with PCCT (even without any appealing symptoms).…”
Section: Methodsmentioning
confidence: 99%
“…Whereas some studies have described quantitative and qualitative activity of PCCT in various countries [9, 18, 19], published data describing this activity in the context of French healthcare system are sparse. In a previous study, we reported the six years’ experience and activity profile of a team which is based in a university hospital [20].…”
Section: Introductionmentioning
confidence: 99%